Pengembangan media praktikum berbasis LabView untuk meningkatkan pencapaian kompetensi berorientasi industri Siswa SMK - Saliruddin Saliruddin; Sapto Haryoko; Hendra Jaya (Seminar Nasional LP2M UNM, 2019)
The objectives to be achieved in this study are: 1) to find out how to develop labview-based practical media that can improve the achievement of industry-oriented competencies in vocational students; 2) To find out how lab design media design is based on labview so that it can improve the achievement of industry-oriented competencies in vocational students; 3) to find out how the results of the development of labview-based practical media applied to vocational students meet the criteria of valid, practical, effective, and efficient. The development model used in this study is the Plomp Development Model (2001) which uses five stages, namely (1) preliminary investigation, (2) design, (3) realization / construction (4) test, evaluation, revision and (5) implementation . From the results of the research and discussion described in the previous chapter, the following conclusions can be made. 1) The steps used in developing LabView-based practicum media are through a needs analysis of the completeness of practicum equipment available at Makassar Vocational High School 10, regarding the process of learning practice in schools, supporting factors for simulation-based learning in schools and student characteristics in schools; 2) The product produced in this study is LabView practical media-based learning; 3) The results of the assessment by material experts, media experts, and programming experts on LabView-based practicum media for media assessment obtained an overall overall score of 4.54 or a very good assessment while the Material aspect obtained a mean score with a score of 4.45 with very good ratings